The population structure of Vibrio cholerae from the Chandigarh Region of Northern India. - Moataz Abd El Ghany; Jagadish Chander; Ankur Mutreja; Mamoon Rashid; Grant A Hill-Cawthorne; Shahjahan Ali; Raeece Naeem; Nicholas R Thomson; Gordon Dougan; Arnab Pain (Public Library of Science (PLoS), 2014)
Cholera infection continues to be a threat to global public health. The current cholera pandemic associated with Vibrio cholerae El Tor has now been ongoing for over half a century.Thirty-eight V. cholerae El Tor isolates associated with a cholera outbreak in 2009 from the Chandigarh region of India were characterised by a combination of microbiology, molecular typing and whole-genome sequencing. The genomic analysis indicated that two clones of V. cholera circulated in the region and caused disease during this time. These clones fell into two distinct sub-clades that map independently onto wave 3 of the phylogenetic tree of seventh pandemic V. cholerae El Tor. Sequence analyses of the cholera toxin gene, the Vibrio seventh Pandemic Island II (VSPII) and SXT element correlated with this phylogenetic position of the two clades on the El Tor tree. The clade 2 isolates, characterized by a drug-resistant profile and the expression of a distinct cholera toxin, are closely related to the recent V. cholerae isolated elsewhere, including Haiti, but fell on a distinct branch of the tree, showing they were independent outbreaks. Multi-Locus Sequence Typing (MLST) distinguishes two sequence types among the 38 isolates, that did not correspond to the clades defined by whole-genome sequencing. Multi-Locus Variable-length tandem-nucleotide repeat Analysis (MLVA) identified 16 distinct clusters.The use of whole-genome sequencing enabled the identification of two clones of V. cholerae that circulated during the 2009 Chandigarh outbreak. These clones harboured a similar structure of ICEVchHai1 but differed mainly in the structure of CTX phage and VSPII. The limited capacity of MLST and MLVA to discriminate between the clones that circulated in the 2009 Chandigarh outbreak highlights the value of whole-genome sequencing as a route to the identification of further genetic markers to subtype V. cholerae isolates.